Sistem Pembuktian Pidana Pada Pelanggaran Hukum Lingkungan di Indonesia - Jailani, Muhammad; Faisal, Muhammad (Universitas Mataram, 2024)
The enforcement of criminal law against environmental violations in Indonesia faces significant challenges, particularly in the effectiveness of the evidence-gathering system. The conventional system, which places the burden of proof entirely on prosecutors, often falls short in addressing complex environmental cases, especially those involving large corporations. Cases like water pollution and illegal logging require complex scientific evidence, such as laboratory analyses and satellite imagery, which are difficult to obtain. This article explores reverse proof systems, where defendants must prove their innocence, although this approach raises concerns about presumption of innocence principles. A risk-based approach is also discussed, prioritizing cases with significant environmental impacts. Technologies like automated sensors and real-time data analysis can enhance evidence collection, but their implementation is limited by infrastructure, budget constraints, and technical skills. The article recommends improving law enforcement capacity, stricter regulations, and leveraging technology to strengthen environmental law enforcemen.